Formal methods of estimating risks in trade - G. P. Fomin (Вестник Российского экономического университета имени Г. В. Плеханова, 2018)
Risks in trade are estimated by absolute or relative level of losses. In absolute terms risk is estimated by the amount of possible loss in material, physical or value (money) term. In relative terms risk can be estimated as an amount of possible loss referred to a certain basis, for example as a property condition of the trade enterprise or total cost of resources on operation or expected profit. In this case the amount of risk is estimated as an occasional deviation of profit or proceeds of sales in direction of drop in comparison with expected values. The article shows specificity of analyzing risks in trade, which is connected with studying losses and revealing damages. The author identifies zones of risks of expected loss values and demonstrates indexes of trade enterprise risks, which should be controlled at all stages of conducting the trade and economic process. By systematizing theoretical and practical material dealing with the said topic an example was provided connected with the use of the totality of formal methods of estimating risks while shaping an optimal product range of goods in the process of distribution of limited funds to make up an order-application for purchasing goods with minimum risk.